A comparative study of antimicrobial prescribing practices for common infectious syndromes among physicians and nurse practitioners in a safety-net hospital - Aakash Balaji; Jessica Hua; Ben Pomerantz; Alfredo J. Mena Lora (Antimicrobial Stewardship & Healthcare Epidemiology)
Antimicrobial prescribing differences between physicians and nurse practitioners (NPs) remain poorly characterized. We compared prescribing practices at a safety-net hospital. NPs adhered more to pneumonia guidelines, while physicians had better adherence for abdominal and urinary infections. Ineffective therapy was more common for NPs. These gaps highlight important stewardship opportunities.